Consumer bankruptcy, mortgage default and labour supply - Wenli Li; Costas Meghir; Florian Oswald (Institute for Fiscal Studies (IFS), 2022)
We specify and estimate a lifecycle model of consumption, housing demand and labor supply in an environment where individuals may file for bankruptcy or default on their mortgage. Uncertainty in the model is driven by house price shocks, education specific productivity shocks, and catastrophic consumption events, while bankruptcy is governed by the basic institutional framework in the US as implied by Chapter 7 and Chapter 13. The model is estimated using micro data on credit reports and mortgages combined with data from the American Community Survey. We use the model to understand the relative importance of the two chapters (7 and 13) for each of our two education groups that differ in both preferences and wage profiles. We also provide an evaluation of the BACPCA reform. Our paper demonstrates importance of distributional effects of Bankruptcy policy.
Keywords: G33; K35; J22; J31; D14; D18; D52; D53; E21; 330; Lifecycle; Bankruptcy; Mortgage Default; Labor Supply; Consumption; Education; Insurance; Moral hazard